Peran Keluarga Dalam Meningkatkan Kualitas Hidup Lansia Di Kota Tanjungpinang - Solina, Emmy; Wisadirana, Darsono; Kuswandoro, Wawan Edi; Chawa, Anif Fatma (Jayapangus Press, 2024)
This study aims to investigate the quality of life of the elderly in Tanjungpinang City through a preliminary study approach. The quality of life for the elderly has become increasingly important in the context of global population aging. A qualitative research method was used, with data collection conducted through a literature review. The results of the literature review were visualized using R-Studio to produce comprehensive assessment review data. The study results show that the quality of life of the elderly in Tanjungpinang City is influenced by various factors. Social factors, such as family support and social interaction, significantly impact their quality of life. Additionally, health aspects also play a crucial role, including accessibility to healthcare services and their physical condition. The study also identifies challenges faced by the elderly in maintaining their quality of life. Some challenges include mobility limitations, chronic health issues, and limited access to social and healthcare services. Economic factors are also a consideration, especially for the elderly living in economically unstable conditions. Family support has a significant impact on the physical, emotional, and social well-being of the elderly. Emotional support from family, such as love and care, has been proven to enhance the happiness and life satisfaction of the elderly. Moreover, assistance with daily activities, such as eating, bathing, and mobility, is vital in maintaining their physical health. The role of family is also evident in the social aspect, where regular and positive interactions between the elderly and family members can prevent feelings of loneliness and social isolation. This study finds that families providing comprehensive support tend to help the elderly achieve a better quality of life. However, challenges such as limited time and resources are also identified as obstacles in elderly care by families.